THE LEGAL POSITION OF THE LAND BANK AND THE APPLICATION OF GOVERNMENT ASSETS IN TERMS OF THE POLITICS OF LAND LAW IN FORCE IN INDONESIA - Yogie Prastiyans; Abdul Salam (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
The Land Bank is an Indonesian legal entity (Sui Generis) established by the central government and given special authority to manage land. Land Banks are basically the same character as Conventional Banks. In Conventional Banks, this institution has an intermediation function as taking and distributing funds from the public. Meanwhile, in the Land Bank, the Central Government and local governments collect land for long-term, medium-term, and annual planning purposes. The problem in this research is how is the position of the Land Bank as the Holder of Land Management Rights in terms of the Politics of Land Law in force in Indonesia and what are the prospects for the utilization of Government assets against the Land Bank as stated in Government Regulation Number 64 of 2021 concerning the Land Bank Agency. This research uses normative juridical research methods through document studies to obtain secondary data. The results of this research explained that the position of the Land Bank in the management of state land assets in the future must be in line with the land politics contained in the constitution and Basic Agrarian Law which aims to realize social justice for all Indonesians. Utilization of Land Bank assets includes land utilization for operational purposes, capital development, and land utilization for distribution purposes, because in principle the land bank prioritizes the principle of non-profit in the development of prospects for the activities of the land bank so that it does not mean that it does not carry out profitable activities but that there is a certain portion for the development of the Land Bank organization.